Efektivitas Amoxicillin dan Piperacillin Terhadap Klebsiella pneumoniae pada Kasus Infeksi Saluran Pernapasan Akut di RSUD Dr. H. Abdul Moeloek Periode 2019 – 2023 - Nadhira Azalia; Tri Umiana Soleha; Ratri Mauluti Larasati; Winda Trijayanthi Utama (CV. Jasa Sukses Abadi, 2026)
Acute respiratory tract infection (ARI) is one of the leading causes of morbidity that often requires antibiotic therapy, with Klebsiella pneumoniae being one of the most commonly found bacterial pathogens and known to have a high level of antibiotic resistance. Irrational use of antibiotics can accelerate the development of resistance, so the effectiveness of antibiotics needs to be evaluated periodically. Amoxicillin and piperacillin are commonly used antibiotics in the management of ARTI. This study aimed to evaluate the effectiveness of amoxicillin and piperacillin against Klebsiella pneumoniae in cases of ARTI at Dr. H. Abdul Moeloek General Hospital from 2019 to 2023. This study is an observational analytical study with a cross-sectional design using secondary data in the form of culture results and antibiotic sensitivity tests from patient medical records. The sampling technique used total sampling with a total of 106 Klebsiella pneumoniae isolates. Data analysis was performed using the Chi-Square test. The results showed that the resistance rate of Klebsiella pneumoniae to amoxicillin was 92.5% with a sensitivity of 7.5%. In contrast, piperacillin showed a higher sensitivity of 58.5% although resistance was still found at 41.5%. Statistical tests showed a significant relationship between the type of antibiotic and the level of bacterial sensitivity (p-value < 0.001). The conclusion of this study indicates that piperacillin is more effective than amoxicillin in the management of ARI caused by Klebsiella pneumoniae and can be considered in the selection of empirical antibiotic therapy.